A biobased self-healing thermoset coating with a dynamic photosensitive molecule. (5th March 2021) - Geelhand de Merxem, Ludovic; Vuluga, Daniela; Lecamp, Laurence
Abstract: A biobased photo-healable thermoset coating has been developed from 4 components in only 2 steps via a solvent-free process involving an epoxy/amine reaction. Its composition includes epoxidized linseed oil and a dynamic molecule (4, 4′-diaminodiphenyl disulfide) which, under UV irradiation, can be photolyzed reversibly. Compared to an analogous material without disulfide bond, this coating exhibits a lower crosslinking density and a higher elongation at break. Importantly, a 100 μm depth scratch has been significantly repaired under UV light: a photo-healable coating having both thermoplastic and thermosetting properties has thus been elaborated. Graphical abstract: A novel class of sustainable biobased thermoset coating exhibiting thermoplastic and self-healing features thanks to a reversibly photocleavable molecule. Image 1 Highlights: A photo-healing coating containing 50 wt-% of fatty compounds has been developed. 4, 4′-Diaminodiphenyl disulfide was chosen as a photo-repair molecule. The coating exhibits a thermoplastic and thermoset behavior. Reversible S–S bonds give a low crosslink density and high elongation at break. A repair of a 100 μm depth scratch has been achieved in 3 h under UV at 100 °C.